Reaching Excellence - Jacob Henry Deacon; Iason-Eleftherios Tzouriadis (Acta Periodica Duellatorum)
The sixteenth-century Collectanea of the condottiero Pietro Monte contains some of the most thorough writings that exist pertaining to the use of staff weapons. A detailed study of how these weapons are categorised, contextualised, and used in Monte’s work can, due to their sometimes limited treatment in other fight books, allow for a comparative approach between Monte’s works and those of other fight book authors. Such a study allows for a more complete understanding of how Monte’s work fits in with the wider fight book genre, properly contextualising the Collectanea, and demonstrating to what extent this important but often overlooked text should be considered revolutionary or reflective of contemporary military and martial trends. In this article is discussed Monte’s approach to defining staff weapons, his contextualisation of staff weapons according to military and martial environments, and Monte’s teachings on the use of staff weapons.